Pictorial Number Sandpaper Media in Recognizing Number Symbols and Training Children's Fine Motor Skills - Krisnawati, Nofi Maria; Ayuningtias, Rindhi; Abusiri; Mubin, Fatkhul; Pifianti, Ade (Universitas Pendidikan Ganesha, 2024)
There are still many children whose development is not optimal, especially in sensory, fine motor, and cognitive development in understanding number symbols. Therefore this study aims to analyze the effectiveness of pictorial number sandpaper media in developing students' sensory, motor, and cognitive abilities in recognizing number symbols 1-10. The method used in this research is mixed method, which combines quantitative and qualitative methods with a sequential approach. The subjects in this study were 20 kindergartens level-A students at Islamic School. Data collection techniques in this study through observation and documentation. The data analysis technique used is the descriptive-analytic technique, which analyzes the variables consisting of cognitive improvement, and fine motor skills through pictorial number sandpapper games. The results showed an increase in fine motor skills and understanding of number symbols. The results of quantitative analysis show an effective increase in the recognition of number symbols from 25% to 100%, which means that children can recognize number symbols well. Likewise, for the results of observational data in training fine motor skills, students experience effective development in fine motor skills, namely, students can improve concentration and focus, improve coordination between hands and eyes, improve visual design skills, improve the ability to control hand and finger movements.